EFL STUDENTS' PERCEPTION OF TEACHER ORAL CORRECTIVE FEEDBACK - St. Fajriana Tahir; Maemuna Muhayyang; Munir Munir (Universitas Negeri Makassar, 2023)
This study aimed to investigate the students’ perception of teacher oral corrective feedback used in the classroom. The method of the research was a descriptive qualitative method. The participants of the study were first-year students of the English Language Education Department, Universitas Negeri Makassar in the academic year 2022/2023. Seven students were selected as the participants using a purposive sampling technique. The instrument of this research was an interview. Thematic analysis was used to analyze the data collected in the interview transcript. Overall, the students have both positive and negative perceptions of oral corrective feedback. The students revealed that they believe oral corrective feedback is needed in their learning performances as it 1) helps the learning progress 2) makes the students aware of the error 3) makes the students feel motivated and appreciated. In contrast, the negative perceptions found from oral corrective feedback are 1) feeling anxious and disappointed 2) reducing self-esteem 3) labelling. Even though students’ perceptions varied, they all accepted every feedback needed for their performances. Lastly, they expected to receive oral corrective feedback with some encouragement and appreciation. Thus, it is concluded the students generally have a positive perception with some notes on teacher oral corrective feedback.